Restless planet - Keach, Stacy; Carroll, Michael (Narrator); Keller, Mark; Coyote, Peter; National Geographic Society (U.S.); National Geographic Television (2011)
"Experience the devastating power of explosive volcanoes, ground-buckling earthquakes, deadly tornadoes, hurricanes and tsunamis as National Geographic heads into the field with scientists who risk their lives to study these fearsome natural phenomena. Featuring over five hours of programming, Restless planet captures extraordinary scenes of destruction from the air, the ground and from inside a tornado and the moving, human side of the story from tales of heroism and tragedy to dedicated teams of experts racing to understand and ultimately better predict the deadly forces of nature."--Container.